Potential Mechanism of Dermal Wound Treatment With Preparations From the Skin Gel of Arabian Gulf Catfish: A Unique Furan Fatty Acid (F6) and Cholesta-3,5-Diene (S5) Recruit Neutrophils and Fibroblasts to Promote Wound Healing - Al-Hassan, Jassim M.; Hinek, Aleksander; Renno, Waleed M.; Wang, Yanting; Liu, Yuan Fang; Guan, Rui; Wen, Xiao-Yen; Litvack, Michael L.; Lindenmaier, Andras; Afzal, Mohammad; Paul, Bincy; Oommen, Sosamma; et al. (Frontiers in Pharmacology, 2020)
Preparations from Arabian Gulf catfish (Arius bilineatus, Val) epidermal gel secretion (PCEGS) effectively heal chronic wounds in diabetic patients. However, specific lipid components of PCEGS that are responsible for various aspects of wound healing are unknown. Here, we report for the first time that, (i) a unique preparation containing only proteins and lipids (Fraction B, FB), derived from the PCEGS accelerated the healing of experimental dermal wounds in female rats (transdermal punch biopsy) in vivo. Histological analyses showed that topical treatment of these wounds with FB promoted the migration of fibroblasts, facilitated the production of extracellular matrix (collagen, fibronectin), induced capillary formation and recruitment of immune cells, and accelerated overall wound healing by day 4 (tested at 1, 2, 3, 4, and 10 days; n=15 for vehicle; n=15 for FB treatment), the lipids responsible for different stages of wound healing were separated into a protein-free bioactive lipid fraction, Ft, which contained a few common long-chain fatty acids, a unique furan fatty acid (F6) and a cholesterol metabolite, cholesta-3,5-diene (S5). Ft (the partially purified lipid fraction of PCEGS), and F6 and S5 present in Ft, proved to be bioactive for wound healing in human dermal fibroblasts. Ft increased the production and extracellular deposition of collagen and fibronectin, ex vivo, (iii) Ft and its subcomponents, pure F6 and S5, also promoted human dermal fibroblast migration into the scratch wound gaps, ex vivo, (iv) Ft, F6 and S5 promoted the recruitment of neutrophils (Green fluorescence protein labeled) to the site of injury in the transected tailfins of transgenic zebrafish, in vivo, (v) Ft, but not F6 or S5, promoted the regeneration of tissues at the wound site in the transgenic zebrafish tailfin, in vivo. Therefore, we conclude that lipid fraction Ft from PCEGS contains the components necessary to promote complete wound healing, and F6 and S5 are responsible for promoting fibroblast and neutrophil recruitment to the site of wounds.